Plan de estrategias competitivas para mejorar el proceso general de cobranza de la cartera vencida del Banco Nacional de Fomento, sucursal Quevedo, período 2010 - Gallo Pallo, Hernán Germánico (2012)
The thesis was conducted in the offices of the National Development Bank, Branch Quevedo, in order to contribute to the improvement of the recovery of loans. Most loans have deteriorated Maturities in purpose, in some cases the client has been plagued by factors that have prevented timely pay their obligations, reaching even to be victims of robbery than it produces or sells, but noteworthy thing is that almost all agricultural loans have collateral, provided the General Regulation of Credit. Not planned and successful strategies have on hand for loan recovery and not manage your collection is that the customer does not pay in many cases even taking how. Clearly, not only the staff that manages the collection of past due loans have to be trained, but also the customer of the institution, which has the obligation to return the money that pays for their economic activity within the deadline. This work found that performing loans and punished the entity is high and dates from many years ago and that the collection efforts of it is small and slow because it does not have a technical planning, so it is necessary the implementation of a Competitive Strategy Plan to improve the recovery of non-performing loans. With the implementation of the Court to replace Coercive Recovery Unit created in recent years, the recovery of claims in this branch would improve, obtaining sufficient liquidity to continue operating in lending to small and medium producers. When developing strategies to discover the amounts will be achieved collectible and uncollectible debt, the debtor that if they can raise their obligations based on the guarantees and difficult recovery values for the existing deficiencies in the placement of money. With the creation of the Court of coercive application of technical administration and special legal regulation that protects the entity have achieved competitive advantages.